The very idea of organization : social ontology today : Kantian and Hegelian reconsiderations - Krijnen, Christian. (Critical Studies in German Idealism, 2015)
The Very Idea of Organization presents a philosophical account of the phenomenon of organization. It takes as its starting point a debate in organization studies about the foundations of organizational research. This debate, however, is running into difficulties regarding the basic concept of the reality that organization studies deal with, that is regarding the ontology of organization. A convincing organizational ontology is not in sight. Therefore, Krijnen introduces a new meta-perspective, offering a more comprehensive and more fundamental social ontology in general as well as an organizational ontology in particular. Exploring the Kantian and Hegelian tradition of philosophy, he convincingly shows that a rejuvenated type of German idealism contains intriguing possibilities for developing a present-day social and organizational philosophy.